Glokalisasi bahasa: Dominasi dan adaptasi slang internasional pada kalangan generasi alpha di ruang virtual - Pahruroji, Muhamad; Mulyati, Yeti; Cahyani, Isah (Universitas Mulawarman, 2025)
This study examines the phenomenon of glocalization of international slang within the Indonesian language as used by Generation Alpha. This research employs a qualitative content analysis approach, focusing on the dominance of glocalization forms, the context of usage, and the underlying reasons for language preferences among Generation Alpha. Based on exploration in virtual spaces, 20 variations of international slang were identified, including suss, savage, insecure, anomali, slay, jump in, flex, vibe, glow up, periodt, simp, bop, FOMO, CMIW, cringe, LOL, ghosting, stan, salty, and spill. The findings show that 75% of these terms underwent a semantic shift through processes such as amelioration, pejoration, generalization, specialization, and association, while the remaining 25% retained their original meanings. The results indicate that the glocalization of slang is primarily influenced by globalization, digital technology, social media, and popular culture. The study further reveals that the family environment and education also play a significant role in shaping these slang language preferences. These findings reflect the social and cultural dynamics of Generation Alpha, who are adept at integrating global linguistic elements into local contexts, thereby creating a unique and dynamic linguistic identity.